Pelindungan Hukum Hak Kekayaan Intelektual Pada Produk Ekonomi Kreatif (Protection Of Intellectual Property Rights On Creative Economic Products) - Sulasi Rongiyati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2018)
As a result of creativity, the creative economy product is an intellectual property that needs to be recognized as an intellectual work that has economic value and gets legal protection. This study analyzes the regulations established by the Government in providing protection against intellectual property rights (IPRs) to ekraf products and the application of such regulations in the city of Surakarta, Central Java and Denpasar City, Bali. Through normative and empirical juridical research methods, secondary and primary data are processed and analyzed qualitatively. The result of the research stated that IPRs protection policy toward creative economy product has been done by the government through IPRs legislations and regional policy related to IPRs protection for creative economy product referring to national policy. Preventive protection is provided through law in the form of economic benefits for the actors who register IPRs of creative economy product. However, the level of public awareness and understanding of the importance of IPRs, the communal nature of creative economy actors in Indonesia, and the nature of IPRs that must be registered for legal protection, cause IPRs protection for creative economy perpetrators is not optimal. At the level of implementation, the awareness and understanding of the perpetrators of the property rights become the key to the success of IPRs protection by the government. The lack of regional alignments has an impact on the not yet optimal economic benefits received by creative economy actors. Therefore, the government should intensify the socialization of IPRs and facilitate the registration of IPRs  for the perpetrators of creative economy. Institutional and regulatory support at the local level is also important to develop and protect the creative economy product.AbstrakSebagai suatu karya kreativitas, produk ekonomi kreatif (ekraf) merupakan kekayaan intelektual yang perlu mendapat penghargaan sebagai suatu karya intelektual yang memiliki nilai ekonomi dan memperoleh pelindungan hukum. Penelitian ini menganalisis mengenai regulasi yang dibentuk Pemerintah dalam memberikan pelindungan terhadap hak kekayaan intelektual (HKI) terhadap produk ekraf dan penerapan regulasi tersebut di kota Surakarta, Jawa Tengah dan Kota Denpasar, Bali. Melalui metode penelitian yuridis normatif dan empiris, data sekunder dan primer diolah dan dianalisis secara kualitatif. Hasil penelitian menyebutkan, kebijakan pelindungan HKI terhadap produk ekraf telah dilakukan oleh pemerintah melalui peraturan perundang-undangan bidang HKI dan kebijakan daerah terkait pelindungan HKI untuk produk ekraf mengacu pada kebijakan tingkat nasional. Pelindungan preventif diberikan melalui UU berupa manfaat ekonomi bagi pelaku ekraf yang mendaftarkan HKInya. Namun, tingkat kesadaran masyarakat dan pemahaman pentingnya HKI, sifat komunal pelaku ekraf di Indonesia, dan sifat HKI yang harus didaftarkan untuk mendapat pelindungan hukum, menyebabkan pelindungan HKI untuk pelaku ekraf belum optimal. Pada tataran implementasi, kesadaran dan pemahaman pelaku ekraf atas kekayaan intelektualnya menjadi kunci keberhasilan pelindungan HKI yang dilakukan oleh pemerintah. Minimnya keberpihakan daerah berdampak pada belum optimalnya manfaat ekonomi yang diterima pelaku ekraf. Oleh karenanya pemerintah perlu menggiatkan sosialisasi HKI dan memfasilitasi pendaftaran HKI untuk pelaku ekraf. Dukungan kelembagaan dan regulasi pada tingkat daerah juga penting dilakukan untuk mengembangkan dan melindungi produk ekraf.